52 The effect of paracetamol legislation on admissions from paracetamol overdose in ireland. (5th April 2017) - Ismail, MS; Christopher, B; Kiat, C; Tatro, E; MacNicholas, R; McCormick, AP; Houlihan, D
Abstract : Background: Paracetamol overdose ( POD) is a prevalent issue worldwide and ease of access has been described as a principal factor for the drug so commonly used. In 2001, Ireland introduced a pack size legislation limiting access to 24-tablets in a pharmacy and 12-tablets in a non-pharmacy setting within a single transaction. To date no study has been published to assess the impact of the legislation at a national level. Aim: The aim of this study is to assess whether the 2001-legislation has reduced hospital admissions from POD in Ireland. Method: Data for POD from 1997 to 2011 was obtained from Healthcare Pricing Office, HSE, which collects data for inpatient admissions to hospitals in Ireland. The data from the five years before and after the legislation was compared (1997-2001vs.2002-2006). Data from 2002–2006 was then compared to a further five years (2007-2011) to assess whether the changes were maintained. Results: There were a total of 14 225 patients admitted from 1997-2006. 7647 patients were admitted from 1997-2001 and 6414 from 2002-2006. There was a statistically significant difference between the mean number of admission during these periods (1529±72.7 vs 1315.6±140.78;p-value 0.0166). From the year 2007-2011, 5719 patients were admitted. When comparing 2002-2006 with 2007-2011, a statistically significant difference was again noted (1315.6±140.78 vs 1143.80±85.73;p-value 0.0481). Conclusions: This study has demonstrated that the 2001-legislation has significantly reduced POD admissions in Ireland. Results of this study can potentially be used as a basis for legislation on other potential harmful substances for example minimum pricing for alcohol which the Irish government is currently reviewing.